German Annual of Spatial Research and Policy 2009 New Disparities in Spatial Development in Europe - Kilper, Heiderose; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The German Annual of Spatial Research and Policy 2009 explores the concept of spatial disparities, which has its roots in national spatial planning and spatial development policy, and discusses new spatial disparities in Europe. The scientific articles provide an overview of the process of formulating a European position on "territorial cohesion" and address some of the issues surrounding new spatial disparities at different levels in different European countries. This includes the transformation from the industrial to the knowledge society, the development of settlement structures, spatial patterns of suburbanisation processes, demographic transformation, and equal ecological living conditions in the European Union.
Preface #x2013; Introduction -- Territorial Cohesion #x2013; Current Views of the Commission and the Member States of the European Union -- From Disparities to Diversity #x2013; Territorial Cohesion in the European Union -- Spatial Patterns in the Knowledge Society -- The Importance of Infrastructures and Interaction Networks for Regional Competitiveness in the Knowledge Economy -- Urbanisation Processes and Regional Disparities in Europe #x2013; The Role of Metropolitan Regions and the Importance of the Settlement Structure -- Suburban Residential Development in Post-socialist Urban Regions: The Case of Moscow, Sofia, and Budapest -- The European Regional Demographic Mosaic #x2013; A Challenge for Spatial Development -- Polarisation or Convergence? Spatial Patterns of Fertility in Hungary 15 Years after the Beginning of the Process of Transformation -- The Subsidiarity Principle #x2013; Does it Impede Equal Ecological Living Conditions in Europe? -- Demographic Change: Complexity as a Challenge for Urban and Regional Development -- Environmental Cooperation across Germany#x2019;s External Borders #x2013; The Case of Ecological Networks -- European Groupings of Territorial Cooperation (EGTC) #x2013; Experiences and Prospects -- Hist. Urban #x2013; Integrated Revitalisation of Historic Towns to Promote a Polycentric and Sustainable Development -- Germany in the Light of the Territorial Agenda #x2013; The ESPON Perspective.
Keywords: Geography; Regional planning; Urban planning; Regional economics; Spatial economics; Human geography; Geography; Landscape/Regional and Urban Planning; Regional/Spatial Science; Human Geography; Electronic books